Interfacial superassembly of MoSe2@Ti2N MXene hybrids enabling promising lithium-ion storage. Issue 36 (28th August 2020) - Zong, Hui; Hu, Le; Wang, Zhenguo; Yu, Ke; Gong, Shijing; Zhu, Ziqiang
Abstract : Our work presents an interfacial superassembly by engineering MoSe2 nanoflowers coupled with ribbon-like Ti2 N MXene frameworks. It can provide a novel synthesis strategy to improve the performance of LIBs. Abstract : In this work, we present an interfacial superassembly by engineering MoSe2 nanoflowers coupled with ribbon-like Ti2 N MXene frameworks (MoSe2 @Ti2 N MXene). The MoSe2 @Ti2 N MXene hybrids have excellent electrochemical performance and are used as anode materials for lithium-ion batteries (LIBs). Etching the Ti2 AlN precursor under different conditions results in two kinds of novel materials with different morphologies: sliced etched-Ti2 N and ribbon-like Ti2 N MXene. Electrochemical analysis indicates that the ribbon-like Ti2 N MXene frameworks not only help to avoid side reactions on carbides in LIBs, but also contribute to the outstanding rate capacity and superior specific capacity, thus achieving ultra-stable long-life cycling performance. The distinctive flower-like MoSe2 can be assembled onto the ribbon-like Ti2 N MXene substrate by the interfacial superassembly. The MoSe2 @Ti2 N MXene electrode reveals a reversible specific capacity of 826 mAh g −1 at a current density of 0.1 A g −1 after 200 cycles. It maintains a capacity of 489 mAh g −1 after 2000 cycles at 1.0 A g −1 indicating satisfactory cycling stability. The new-type interfacial superassembly can provide a novel synthesis strategy for anode electrodes to improve the performance of LIBs.